The first case of congenital syphilis diagnosed by 16S ribosome-RNA gene sequence analysis. Issue 2 (February 2022) - Ono, Yosuke; Okumura, Ryo; Hatanaka, Kanako C.; Sato, Yuichiro; Ota, Hajime; Fukushi, Yoshiyuki; Wada, Shinichiro; Yamada, Hideto
Abstract: Syphilis infection during pregnancy causes perinatal complications and mother-to-child transmission if untreated. A newborn was delivered by emergent cesarean section due to non-reassuring fetal status at 34 weeks of gestation. The mother tested negative for rapid plasma reagin (RPR) and Treponema pallidum hemagglutination (TPHA) in early pregnancy. The newborn had a severe inflammatory reaction, thrombocytopenia, and elevated IgM as well as disseminated intravascular coagulation and multiple organ failure. The 16S ribosomal RNA gene sequence analysis of the amniotic fluid detected Treponema pallidum . The newborn tested positive for RPR, TPHA, and IgM fluorescent treponemal antibody-absorption in the blood, and thus, congenital syphilis was diagnosed. This is the first case that 16S ribosomal RNA gene sequencing of the amniotic fluid led to an early diagnosis of congenital syphilis in a newborn. The 16S rRNA gene sequencing may be a useful method for the early detection of the primary causative microbe of congenital infection.